Effects of optogenetic stimulation of vasopressinergic retinal afferents on suprachiasmatic neurones - Hume, Catherine; Grinevich, Valéry (Journal of neuroendocrinology, 2019)
Physiological circadian rhythms are orchestrated by the hypothalamic suprachiasmatic nucleus (SCN). The activity of SCN cells is synchronised by environmental signals, including light information from retinal ganglion cells (RGCs). We recently described a population of vasopressin-expressing RGCs (VP-RGC) that send axonal projections to the SCN. To determine how these VP-RGCs influence the activity of cells in the SCN, we used optogenetic tools to specifically activate their axon terminals within the SCN. Rats were intravitreally injected with a recombinant adeno-associated virus to express the channelrhodopsin-2 and the red fluorescent protein mCherry under the vasopressin promoter (VP-ChR2mCherry). In vitro recordings in acute brain slices showed that approximately 30% of ventrolateral SCN cells responded to optogenetic stimulation with an increase in firing rate that progressively increased during the first 200 seconds of stimulation and which persisted after the end of stimulation. Finally, application of a vasopressin V1A receptor antagonist dampened the response to optogenetic stimulation. Our data suggest that optogenetic stimulation of VP-RGC axons within the SCN influences the activity of SCN cells in a vasopressin-dependent manner.